2016
DOI: 10.1016/j.ccell.2016.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Liver Cancer Prevention in Cirrhosis by Organ Transcriptome Analysis and Lysophosphatidic Acid Pathway Inhibition

Abstract: SUMMARY Cirrhosis is a milieu that develops hepatocellular carcinoma (HCC), the second most lethal cancer worldwide. HCC prediction and prevention in cirrhosis are key unmet medical needs. Here we have established an HCC risk gene signature applicable to all major HCC etiologies: hepatitis B/C, alcohol, and non-alcoholic steatohepatitis. A transcriptome meta-analysis of >500 human cirrhotics revealed global regulatory gene modules driving HCC risk and lysophosphatidic acid pathway as a central chemoprevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
256
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 189 publications
(266 citation statements)
references
References 41 publications
6
256
2
2
Order By: Relevance
“…Hepatocyte-derived autotaxin (ATX) catalyzes production of LPA that activates LPA receptor 1 (LPAR1) on HSCs, and increased ATX in various chronic liver diseases has been association with poorer prognosis and cancer risk, [185, 186]. Pharmacological and/or genetic inhibition of ATX and/or LPAR1 attenuates HSC activation and reduces liver fibrosis and cancer in rodent models [185, 186]. …”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatocyte-derived autotaxin (ATX) catalyzes production of LPA that activates LPA receptor 1 (LPAR1) on HSCs, and increased ATX in various chronic liver diseases has been association with poorer prognosis and cancer risk, [185, 186]. Pharmacological and/or genetic inhibition of ATX and/or LPAR1 attenuates HSC activation and reduces liver fibrosis and cancer in rodent models [185, 186]. …”
Section: Mechanisms Of Hsc Activationmentioning
confidence: 99%
“…Animal models based on chemical, surgical, and/or genetic interventions have been criticized for their physiological and/or clinical irrelevance [329]. However, unbiased omics-based characterization could enable identification of models that recapitulate specific molecular dysregulation of interest [186]. In addition to these advancements, systematic strategies to translate the experimental model-based findings to clinically meaningful long-term consequences in human fibrotic liver diseases will substantially increase the chance of success in the clinical evaluation of candidate antifibrotic therapies [186].…”
Section: Summary and Future Directionmentioning
confidence: 99%
“…A SNP in MPO encoding an antioxidant enzyme was associated with HCC risk in a prospective cohort of HCV cirrhotics [46]. A transcriptomic signature in diseased liver, now available as a Laboratory Developed Test (LDT), has been validated as a pan-etiology HCC risk predictor in patients with chronic hepatitis B/C, alcohol abuse, or non-alcoholic steatohepatitis (NASH) [4750]. …”
Section: From One-size-fits-all To Tailored Hcc Surveillance Strategymentioning
confidence: 99%
“…The role of ATX-LPA signaling in liver carcinogenesis had not been examined until recently however. To explore pan-etiology targets for HCC chemoprevention, we performed regulatory gene network modeling by synthesizing genome-wide transcriptome profiles of clinical fibrotic/cirrhotic liver tissue (n = 523) 8 . The transcriptome meta-analysis identified 31 tightly co-regulated gene modules forming two major groups connected by three central hub modules.…”
mentioning
confidence: 99%
“…In fact, treatment of rats in a diethylnitrosamine (DEN) model of hepatic fibrosis and HCC, that has been shown to closely resemble human disease, 9 with either an ATX inhibitor (AM063) or an LPAR1 antagonist (AM095) resulted in decreased histological fibrosis and reduced HCC development, establishing for the first time an association between ATX-LPA signaling and hepatocarcinogenesis 8 . More recently, it was shown that hepatocyte-specific Atx -deficient mice are protected from both fibrosis development in response to carbon tetrachloride (CCl 4 ), and HCC development in response to a single injection of DEN and repeated administrations of CCl 4 , thus confirming our original findings 10 …”
mentioning
confidence: 99%